Inconvertibility Loss And Murabaha: A Recovery Option for Islamic Political Risk Insurers - Mohamed El-Fatih Hamid; Mirghani Hassan (Usim Press, 2024)
Malaysian Journal of Syariah and Law (MJSL) Volume 11 No.2 Page (202-214)